"Dusky powder magazines": the Creole revolt (1841) in nineteenth century American literature - Bernier, Celeste-Marie (2002)
This thesis examines literary and historical accounts of the Creole slave ship revolt (1841) by Frederick Douglass, William Wells Brown, Lydia Maria Child and Pauline E. Hopkins. The introduction debates the generic status of government testimony and press reportage and identifies the fundamental theoretical issues of the dissertation which include those of intentionality, intertextuality and "signifyin(g)." Chapter I traces the traditions of black and white abolitionism which influenced Douglass's adaptations of the mutiny and researches his representations of the heroic slave figure, Madison Washington, in speeches which he gave in Britain and America during the 1840s. Chapter II analyses the major critical questions surrounding Douglass's. The Heroic Slave (1853) while exploring its previously neglected theatrical conventions. This chapter also compares this work with Douglass's recently discovered second version, The Heroic Slave: A Thrilling Narrative of the Adventures of Madison Washington in Pursuit of Liberty (1853/63? ). Chapter III contextualises Brown's (re)modelling of the black historical figure by examining the varying types of forum - including both periodical and historical volumes - within which he published "Madison Washington" (1861,1863) and "Slave Revolt at Sea" (1867). This chapter discusses Brown's experimentation with an antislavery panorama and interweaving of literary, biographical and historical techniques to revise existing formal conventions. The final chapter interprets Child's biography of "Madison Washington" published in The Freedmen's Book (1866), and Hopkins's short story, "A Dash for Liberty" (1901), in terms of their interventions into gendered representations of slave heroism. Child's text is considered alongside her earlier journalism on the Creole revolt and her short story on insurrection, "The Black Saxons" (1846), and contextualised by an analysis of its publication in an educational tract. This chapter also discusses Hopkins's "Famous Men and Women of the Negro Race" (1901-2), and her textual borrowings from Brown's "Slave Revolt at Sea" (1866) to demonstrate the political imperatives guiding her dramatisations of black history. Finally, the conclusion explores the mid-twentieth century version of this revolt, Madison (1956), a musical composed by the black playwright, Theodore Ward, to indicate the importance of this approach for re-evaluating intertextual relationships across black and white abolitionist authors, throughout the nineteenth century and after.